FAKTOR RASIO KEUANGAN TERHADAP RETURN SAHAM PERUSAHAAN FOOD AND BEVERAGES YANG TERDAFTAR DI BEI - Wirawan, Nicholas Edric; Nababan, Tiorika; Putri, Arie Pratania; Ong, Valensia; Hilda, Sella; Silalahi, Alistraja Dison (Fakultas Ekonomi Prodi Akuntansi, 2024)
ABSTRACT This study aims to find important financial ratio factors such as profitability, solvency, liquidity, and other financial ratios that have a significant effect on the return (Return of Shares) of a company in the food and beverage sector for the 2017-2021 period listed on the Indonesia Stock Exchange. The research method uses quantitative descriptive with a quantitative approach to examine population data or samples in the form of numbers with statistics as a measuring tool and testing research hypotheses. The research data comes from the annual report listed on the Indonesia Stock Exchange. The population collected is 15 food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the 2017-2021 period. With the selection with Purposive Sampling Technique, 8 companies were obtained with a total of 40 samples. The results of this study show that the sample tested does not have a significant effect on the rate of return (Stock Return) of a company. Keywords: Financial Ratios, Stock Return, Profitability, Solvability, Liquidity